Using the properties of logarithms, we can rewrite the equation as:
log_4(x(x+6)) = 2
Using the logarithmic property log_a(b) = c can be rewritten as a^c = b:
4^2 = x(x+6)
16 = x^2 + 6x
Moving all terms to one side, we get:
x^2 + 6x - 16 = 0
We can solve this quadratic equation by factoring:
(x + 8)(x - 2) = 0
Setting each factor equal to zero:
x + 8 = 0 or x - 2 = 0
x = -8 or x = 2
However, we cannot take the logarithm of a negative number, so the only valid solution is x = 2.
Solve for the equation:log_4 x+log_4(x+6)=2
1 answer